1997
DOI: 10.1164/ajrccm.155.6.9196122
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of summer air pollution on respiratory health of asthmatic children.

Abstract: In the early summer of 1995, the acute respiratory effects of ambient air pollution were studied in a panel of 61 children, ages 7 to 13 yr, of whom 77% were taking asthma medication. Peak flow was measured twice daily with MiniWright meters at home and the occurrence of acute respiratory symptoms and medication use was registered daily by the parents in a diary. Exposure to air pollution was characterized by the ambient concentrations of ozone, PM10, and black smoke. During the study period, maximal 1-h ozone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
78
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 2 publications
11
78
0
Order By: Relevance
“…In two other panel studies [23,24] conducted in Mexico City, Mexico, where there are high levels of pollution, symptoms and decreases in PEF were associated with O 3 and PM10 levels. In a study conducted in the Netherlands [25], BS was associated with a decrease in PEF, acute respiratory symptoms and medication use. Weaker associations were found for PM10 and O 3 levels.…”
Section: Discussionmentioning
confidence: 97%
“…In two other panel studies [23,24] conducted in Mexico City, Mexico, where there are high levels of pollution, symptoms and decreases in PEF were associated with O 3 and PM10 levels. In a study conducted in the Netherlands [25], BS was associated with a decrease in PEF, acute respiratory symptoms and medication use. Weaker associations were found for PM10 and O 3 levels.…”
Section: Discussionmentioning
confidence: 97%
“…However, European research has had access to black smoke measurements. A panel study of 61 (77% on asthma medications) children in the summer showed stronger associations for black smoke than for PM 10 in relation to PEF, respiratory symptoms, and bronchodilator use (94). The authors hypothesized that black smoke may be a better surrogate for fine particles emitted by diesel engines or for other chemicals that may be the causal components in DE.…”
Section: Epidemiologic Evidence For Pollutant Mixtures Containing Pahmentioning
confidence: 99%
“…In population studies, effects of air pollution have been associated with asthma morbidity and exacerbation ofsymptoms. Increased hospitalizations (1,2), emergency room and dinic visits (3,4), and medication use (5) due to asthma attacks, as well as decreased peak flow measurements (6) in asthmatics, have been associated with air pollution. However, the relationship between the prevalence of asthma and air pollution has yet to be proven.…”
mentioning
confidence: 99%